The Validity of Heart Rate Variability Obtained from Electrocardiography and Blood Pressure in Rats Subjected to Isoproterenol-Induced Heart Ischemia - Maryam Farokhipour; Farzaneh Ketabchi (Journal of Tehran University Heart Center, 2023)
Background: Heart rate variability (HRV) is calculated by electrocardiography (ECG-HRV) or blood pressure (BP-HRV). The purpose of this study was to determine the validity of the above methods in rats with normal and ischemic hearts during the baroreflex maneuver.